2009
DOI: 10.3109/19396360903114429
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Metallothionein-1 (MT-1) mRNA in the Rat Testes and Liver After Cadmium Injection

Abstract: Metallothioneins (MTs) belong to the family of stress proteins that are present in the majority of living organisms. The MTs play an important task in detoxifying heavy metals. The mammalian scrotal testis is known to be susceptible to cadmium (Cd) exposure. The present work focuses on the MT-1 isoform and aims to ascertain and confirm previous findings to answer whether rodent testes indeed contain MT-1 mRNA, whether its level is increased with Cd injection in liver and testes, and lastly what is the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Plants and crops grown in soil treated with Cd 2+ contaminated fertilizers, sewage effluent and sewage sludge, negatively impact human health 36. Notably, the testes are prone to Cd 2+ exposure 7,10,37; however the mechanisms of toxicity are complex. In the present study, CdCl 2 exposure significantly decreased the activities of testicular (3β‐HSD) and (17β‐HSD), the crucial enzymes necessary for androgens biosynthesis 38.…”
Section: Discussionmentioning
confidence: 99%
“…Plants and crops grown in soil treated with Cd 2+ contaminated fertilizers, sewage effluent and sewage sludge, negatively impact human health 36. Notably, the testes are prone to Cd 2+ exposure 7,10,37; however the mechanisms of toxicity are complex. In the present study, CdCl 2 exposure significantly decreased the activities of testicular (3β‐HSD) and (17β‐HSD), the crucial enzymes necessary for androgens biosynthesis 38.…”
Section: Discussionmentioning
confidence: 99%
“…93 In the case of Wistar rats, parenteral cadmium(II) application led to increasing MT expression in liver and testes as 2.16 fold increased MT expression was detected six hours after cadmium(II) application. 98 Exposition to cadmium(II) ions may be detected in human peripheral blood lymphocytes. MT expression shows correlation between Cd(II) exposition and renal dysfunction.…”
Section: Cadmiummentioning
confidence: 99%
“…X-ray diffraction results together with NMR data have established that the metals are tetrahedrally coordinated in two isolated domains in mammalian Cd-7-MT and Zn-7-MT, and recently, combination of 113 Cd NMR, CD and mass spectrometry showed that domain of MT was capable of binding more than 5 Cd 2+ ions [33]. mRNA RT-PCR human peripheral blood lymphocytes [234] semi-quantitative RT-PCR rat testes and liver (Cd injection) [235] RT-PCR mouse cerebral cortex [236] HPLC-ICP-TOF-MS cytosols of gibel carp [141] RT-PCR ,Western blotting AML-2 cell line [237] CE horse kidney [238] MT 1 CE-ICP rabbit liver [239] mRNA QRT-PCR in situ prostate tissue [240] real-time PCR HeLa cells [241] 2D micro HPLC-ICP-MS RT-PCR isoform-specific knockdown cells [142] saturation with cadmium chloride, ion-exchange HPLC, Western blot AAS-ICP human placenta [242] Immunohistochemical staining Real time RT-PCR, immunoblot human breast and the MCF-10A cell line [243] ELISA in plasma of humans and experimental animals (rabbit, mouse rat) [244] SDS-PAGE, Western blot immunofluorescence staining prostate cells (BPH, PC-3 and HPR-1 cells) [48] RT-PCR agarose gel electrophoresis CD61 + megakaryocytes [245] real-time PCR liver tissue of lake trout [246] cadmium-hemoglobin assay real-time RT-PCR liver and kidney tissue, blood of human and rats [247] tryptic digestion, MALDI-TOF/TOF MS RWPE-1 cells derived from normal human prostate epithelium [197] Western blotting superoxide dismutase 1 transgenic (SOD1 Tg) mouse [248] RT-PCR and in situ hybridisation hippocampus of old rats [249] quantitative real-time RT-PCR breast cancer cell lines [250] MT 1 and 2 real-time RT-PCR keloid keratinocytes [251] semi-quantitative RT-PCR -densitometry scanning ELISA AAS testicular interstitial cells (Sprague-Dawley rats) [36] CZE cytosol of the pancreas and liver in mice [124] anion-exchange HPLC, RP-HPLC MALDI-TOF-MS rabbit liver [252] RT-PCR bone tissue of rats [253] RT-PCR dental pulp of rat incisors [254] immunohistochemistry hyperplastic...…”
Section: Metallothionein Structurementioning
confidence: 99%